Optimal Control of Begomovirus–Whitefly Dynamics in TomatoCrops - Michel, IDO; Michel, IDO (Optimality, 2026)
Tomato Yellow Leaf Curl Virus, transmitted by the whiteflies Bemisia tabaci, severely threatens global tomato Production. Conventional stratégies often fail to address complex interaction between Vector population, virus transmission, and management intervention s.  We develop an epidemiological model integrating tomato plant Dynamics, whiteflies populations, and TYLCV spread to evaluate integrated management stratégies including biological control , removal of infected plants, resistant varietes, and insect- prof nets. Control policies are optimized via Pontryagin's Maximum Principle to minimize economic losses. Simulation show that combining all stratégies is most cost effective under high infection scénario, whereas relying soley on resistant varieties may increase selective pressure on vectors. Early Season prevention benefits particularly from biological control, infected plants removal, or insecte nets . Overall, optimized integrated management reduces TYLCV incidence, improves plants survival, and lowers pesticides use, providing a sustainable and economically viable approach